1986
DOI: 10.1111/j.1399-3054.1986.tb01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fruit load and environmental factors on nitrate reductase activity and on concentration of nitrate and carbohydrates in leaves of eggplant (Solanum melongena)

Abstract: Both the in vivo (+ nitrate) nitrate reductase (NR) activity (leaf disks incubated in the presence of KNO3) and the in vivo (− nitrate) NR activity (leaf disks incubated without KNO3) in leaves of eggplant (Solanum melongena L. cv. Bonica) were affected by rapidly growing fruits. Plants with a fruit load showed more pronounced diurnal variation in (+ nitrate) NR activity and higher (− nitrate) NR activity than plants without fruit. The higher (− nitrate) NR activity was accompanied by higher nitrate and lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…The activity of NR has often been shown to Tab. 4 (Claussen, 1986). A positive correlation between NR activity and NO 3 concentration in the leaf tissues implies that the activity of NR is induced by increasing NO 3 concentration, as it has been reported by Sivaasankar and Oaks (1996).…”
Section: Methodssupporting
confidence: 55%
“…The activity of NR has often been shown to Tab. 4 (Claussen, 1986). A positive correlation between NR activity and NO 3 concentration in the leaf tissues implies that the activity of NR is induced by increasing NO 3 concentration, as it has been reported by Sivaasankar and Oaks (1996).…”
Section: Methodssupporting
confidence: 55%
“…With a low nitrate supply NRA of leaves is generally lower than that of the roots (Andrews, 1986;Pate, 1983;Smirnoff and Stewart, 1985). NRA in young leaves was higher than in old and intermediate leaves, as generally observed (Carelli and Magalhaes, 1981;Claussen, 1986;Doddema et aL, 1986). But after week 10 this difference disappeared, again suggesting that hardly any newly absorbed nitrate reached the leaves from then on.…”
Section: Nitrogen Depletion In Plantago 203supporting
confidence: 61%
“…2), and the nitrate content of the leaves increased when little or no nitrate was detectable in the leaves of plants without fruits (Claussen, 1986). It was concluded that the higher concentrations of nitrate in leaves of eggplants with fruits were due to their low carbohydrate content, which in turn had been caused by the rapid transport of photosynthates to the growing fruit (Claussen, 1986). Since, in contrast to nitrate, an accumulation of large quantities of ammonium nitrogen in leaves did not occur, fruit-bearing plants must have detoxified this nitrogen after its absorption from the nutrient solution.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of fruit growth, eggplants also accumulate nitrate in the leaves. However, as soon as fruits are removed, the concentration of nitrate falls rapidly (Claussen, 1986). The decrease in nitrate concentration is accompanied by an increase in the carbohydrate level in leaves followed by the initiation of vegetative growth and flower set.…”
Section: Introductionmentioning
confidence: 99%